On the difficulties of translating headlines in the medical scientific literature - Nerush, A. V.; Неруш, Алла Володимирівна (Stuttgart, Germany : ORT Publishing, 2019)
Scientific work at a higher educational establishment is a stable factor in increasing the motivation of learning a foreign language. It is an integral part of any research to read and translate special articles. Reading is included in the sphere of communicative and social activity of a person, and it plays an extremely important role, since it opens up access to the most up-to-date information sources for a specialist and, thus, is one of the main means of satisfying his cognitive needs and carrying out professional activities. Like any activity, reading is always purposeful; its goal is to extract information necessary for professional development. Reading situations are very different: sometimes it is necessary to only determine what the article is about; in other cases, along with an understanding of the certain facts, to catch all the details; finally, to understand exactly the content. The main characteristics of the understanding of the text are completeness, accuracy and depth. Characteristic features of the scientific style are its information content, consistency, accuracy and objectivity. The reader faces numerous lexical and grammatical difficulties. But even at the stage of searching for the necessary information, the first thing he pays attention to is the headline of the article.